Taiwan's democracy on trial political change during the Chen Shui-bian era and beyond - Copper, John F. (The Rowman & Littlefield Publishing Group, 2010)
In Taiwan's Democracy on Trial, Professor Copper assesses the process of democratization in Taiwan during the Chen Shui-bian Era (2000 to 2008) and after. He shows that in several respects, most important being press freedom, human rights, ethnic relations, political reform, constitutionalism, and clean governance, democratization regressed. Economic management was not good and relations with the United States were severely strained, which also hurt the Chen administration and explains why the Nationalist Party returned to power in 2008. The democratization process has improved since 2008.